ADVANTAGES OF DEEP-SOIL TILLAGE OF WINTER WHEAT FIELDS - V.Ortikov, N.Saidov, M.Xidirov, D.B.Irgashev (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
Tine seeders are recognised for their greater soil disturbance at seeding, relative to disc seeders. Aspects of soil disturbance at seeding include furrow size and depth as well as the extent of soil movement or soil throw. The lateral soil throw (i.e. the sideways movement of soil pushed out of the furrow) is a particularly important parameter to consider in a no-till seeding context. A limited amount of lateral soil throw at seeding is typically desired to mechanically incorporate soil applied herbicides. However, excessive soil throw limits the furrow backfill, reducing soil cover over the seed, and creates interactions (ridging) between adjacent seed rows, resulting in additional soil cover which increases seeding depth and potentially induces crop damage from herbicides.